Influence of graphene and multi-walled carbon nanotube additives on tribological behaviour of lubricants - Singh, R.; Dixit, A.; Sharma, A.; Tiwari, A.; Mandal, V.; Pramanik, Alokesh (2018)
In the present study, the tribological performance of water-based emulsion (lubricant) was investigated by blending carbon fillers such as graphene nanoplatelets and multiwall carbon nanotubes using pin-on-disc tribometer. It was noticed that addition of GnP and MWCNT in water-based emulsion (conventional lubricant) increases the thermal conductivity and viscosity as compared to conventional lubricants. The nanolubricants were supplied with minimum quantity lubrication (MQL) technique at a constant flow rate and pressure in the sliding zone. The addition of 0.8 wt.% concentration of GnP showed 58.39% reduction in coefficient of friction and 61.80% reduction in wear depth compared to the conventional lubricant. Similarly, for 0.8 wt.% concentration of MWCNT showed 26.27% reduction in coefficient of friction and 47.35% reduction in wear depth compared to the conventional lubricant. The sliding surface micrographs were also investigated to explain the synergistic effect of nanoparticles.